Ekplanation of Multimedia Counseling about Prevention of Anemia on Adolescent Girls Behavior in Prevent Adolescent Anemia - Mia Dwi Agustiani; Heru Subaris Kasjono (POLTEKKES KEMENKES YOGYAKARTA, 2024)
The way to break the chain of transferring stunting is the planting of healthy living and healthy consumption of balanced nutrition in young women, bearing in mind that the next generation of the nation will be strong and healthy if needed by mothers with health conditions. The development of an effective health promotion program through health education with the Android application is expected to provide information and assist young women to be better in their health, improve the health of young women, learn about nutrition, anemia, and healthy life behavior so that they can anticipate early stunting events. Multimedia counseling is a method of learning that involves audio, visual and discussion to make it more interesting and easy to understand. This study analyzed the explanation of multimedia counseling about the prevention of anemia on adolescent girls behavior to prevent anemia. This study used pretest-posttest with control group design, with a quasi-experimental. The study population was 259, the samples were 90 respondents who were assigned to two groups. The samples were selected by simple random sampling. Respondents were given multimedia counseling about anemia prevention, a behavioral questionnaire, and FFQ. A capillary blood test was conducted using Quik-Check, and the respondents were followed up every week and evaluated for 5 weeks. Results were tested using T-Test and linear regression. Multimedia counseling had an effect on knowledge (t = 3.097; CI = 95%; 2.229-10.215; p value = 0.003), attitude (t = 9.56; CI = 95%; 10.055-15.331; p value = 0.001), behavior (t = -2.22; CI = 95%; -4.628- -0.260; p value = 0.029), FFQ (t = -2.18; CI = 95%; -4.883 - -0.227; p value = 0.032) and BMI (t = -10.40; CI = 95%; - 5.094 - -3.460; p value 0.001) among adolescent girls in preventing anemia with R-Square of 0.952 (95%). There was an explanation of video counseling on the increase in knowledge, attitudes, behavior in preventing adolescent anemia. Provision of ongoing multimedia counseling and monitoring of female careers in preventing adolescent anemia needs to be improved. Therefore, the role of healthcare providers for monitoring and evaluation is very necessary.